EFFECT OF DIFFERENT PROBIOTIC BACTERIA ON SURVIVAL RATE, GROWTH, AND PRODUCTION OF WHITELEG SHRIMP IN TRADITIONAL-PLUS TECHNOLOGY - Muharijadi Atmomarsono; Endang Susianingsih (Indonesian Aquaculture Journal, 2015)
Instead of culturing tiger shrimp that is frequently burdened by mass mortality, whiteleg shrimp (Litopenaeus vannamei) is then considered as an alternative commodity in Indonesian brackishwater ponds. To prevent the whiteleg shrimp from diseases, different probiotic bacteria were tested in completely randomized design experiment using nine 250 m2 experimental ponds stocked with 10 PLs of whiteleg shrimp fry/m2. Three treatments were applied, namely A) alternate use of probiotic bacteria RICA-1, RICA-2, RICA-3; B) alternate use of probiotic bacteria RICA-4, RICA-5, RICA-3, and C) control (without probiotic bacteria); each with three replications. After 11-week application, the results showed that the best survival rate of whiteleg shrimp was achieved by treatment B 98.83%) and the best production was achieved by treatment A (23.52 kg/250 m2). However, there were no significant differences (P>0.05) among the three treatments tested for the shrimp survival rate. The whiteleg shrimp production in treatment A and B were signicantly better (P<0.05) than that in treatment C (control). These high shrimp production in treatment A and B were mainly caused by the capability of the applied probiotics in controlling some water quality variables and Vibrio numbers.